Mathematics Creative Thinking Skill Viewed from the Student Life Skill in SAVI Model Based ICT - Octaviani, Dessy; Dwijanto, Dwijanto; Ahmadi, Farid (Universitas Negeri Semarang, 2019)
The background of the research was poor response of students toward the given stimulus by teacher in the form of exercise question and the answer of the question. This condition required teacher to think and act creatively to solve the students’ difficulties. One of them could be done by using learning model to facilitate students in sharing responses dealing with materials or tasks given by the teacher in the form android application. It would facilitate students to think and present creative answers. The objective of this research was to analyze the effectiveness of SAVI model based ICT toward mathematics creative thinking skill of students seen from their life skill. This mix method research was typed sequential explanatory. The procedures to collect the data were qualitative and quantitative. The population consisted of all fifth graders of SD Islam Al–Azhar 25 Semarang. The samples were selected by purposive sampling. There were VA and VB students of the school, consisting of 60 persons as experimental group. While, VC and VE students of the school, consisting of 60 students were grouped as experimental group. The technique of collecting the data was test. The findings showed that mathematics creative thinking skill of experimental group was better than control group. Mathematics creative thinking skill and their life skills were categorized high, moderate, and poor. The categorization showed that mathematics creative thinking of the students had different mastering indicators seen from their life skills.